Pengaruh Keterlibatan Fesyen terhadap Kepercayaan Merek dengan Mediasi Nilai Hedonis dan Nilai Utilitarian pada Konsumen Gawai, Tablet dan Laptop - Afrima Widanti; Lizar Alfansi (Jurnal Bisnis dan Ekonomi, 2019)
Trust has been recognized as an important factor in business. There are many factors that influenced brand trust such as fashion involvement, hedonic value, and utilitarian value. The purpose of this study was to analyze the influenced of fashion involvement toward brand trust through hedonic value and utilirarian value. The data of respondent consumers of Smarthphone, Tab and Notebook were collected by questionnaires mailed to the respondents. Total respondents is 163. This research use Structural Equation Modelling AMOS to analysis. This research found that brand trust is significantly affected by fashion involvement through hedonic value and utilitarian value, fashion involvement has a positive effect on hedonic value and utilitarian value. The new finding is brand trust is not significantlu influenced b fashion involvement